The Tradition of Mujahadah Solawat Ummi by the Community of Danawarih Village Balapulang District, Tegal Regency (A Phenomenological Study of Mujahadah Solawat Ummi) - Vika Fitrotul Uyun (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2025)
This Ummi Sholawat Mujahadah was held in Danawarih Village, Balapulang District, Tegal Regency. This Ummi Sholawat Mujahadah is a medium to get closer to Allah SWT. Mujahadah helps us in low self-awareness towards higher awareness. This study reveals these meanings through a phenomenological perspective and analyzes them with a psychological therapist so that it can be used as an understanding for the practitioners of Ummi sholawat mujahadah so that they can take psychological benefits for their lives. The data collection techniques are by observation, interviews and documentation. While the study in this study is how the Ummi Sholawat Mujahadah Tradition in Danawarih Village (Phenomenological Study in Ummi Sholawat Mujahadah). The results of this study are that this Ummi Sholawat Mujahadah is very important for human life. Especially for the congregation who always practice the Ummi sholawat Mujahadah with the aim of getting closer to Allah SWT. The purpose of this study is to describe the Ummi Shalawat Mujahadah performed in Danawarih Village and to understand its symbolic and philosophical meaning